El Niño and cereal production shortfalls: Policies for resilience and food security in 2016 and beyond - Dorosh, Paul A.; Kennedy, Adam; Torero, Máximo (International Food Policy Research Institute, 2016)
The current El Niño episode may be among the strongest on record (Earth Institute 2015). This year again, serious localized production shortfalls have occurred or are expected, creating an urgent need for policy actions to ensure adequate food supply and food mobility from surplus to deficit regions. Although global cereal production is not expected to decline significantly, complacency is not warranted: The situation calls for careful monitoring of production and prices, promotion of transparent international and domestic trade policies, and expanded coverage of safety nets and nutrition programs for the households most severely affected, all while working toward long-term improvements in resilience and agricultural production.